PENGOPTIMALAN PROGRAM LINK AND MATCH BAGI MASA DEPAN MAHASISWA PENDIDIKAN VOKASIONAL - Satria Ramdhani (CV. ADIBA AISHA AMIRA, 2024)
In the process of progressing a nation, one of the most important parts is the existence of quality human resources (HR) who have equal knowledge and expertise in all fields, so that quality human resources can be obtained and have competent skills. Therefore, vocational education must be able to keep up with the development of business and industry. This article is conducted using research with the Literature Review method, which is a review and critical evaluation of previously existing sources and conducts discussions that are relevant to the research topic. This approach is carried out to describe the results of the analysis carried out on various sources such as journals, books, papers that discuss factors related to the topic of this research, namely the optimization of link and match programs in Vocational Education. This research provides information that the role of DUDI is very important in helping to realize the achievement of human resources who have competent skills.